Thermaly Active Interior Panels with an Integrated Active Area - Kalús Daniel; Kurčová Mária; Straková Zuzana; Kubica Matej (Slovak Journal of Civil Engineering, 2021)
Panels with an integrated active area can be used for interior applications for walls, ceilings and floor heating, and alternatively as a wet or dry type of construction. At present, most panels with an integrated active area are made of gypsum boards with milled channels and embedded pipes. Some manufacturers already supply these panels with thermal insulation (Radwan et al., 2021; Zhang et al., 2020). Certain limitations, mainly regarding the diameter and material of the pipes, apply to the panels with channels milled in the gypsum board and embedded pipes. These limitations are closely related to the high cost of such panels and to the limited heat/cooling output. The disadvantages of these panels are eliminated by the construction of a thermal insulation panel with active thermal protection for application with an active heat transfer control system (indoor thermally active panel (ITAP)) in accordance with European Patent No. EP 2 572 057 B1 (Kalús, 2011).